Respuesta :

Answer:  7

=======================================================

Explanation:

The result of [tex]g^{-1}(-8)[/tex] is the same as trying to find x in [tex]g(x) = -8[/tex]

Draw a horizontal line through -8 on the y axis. This horizontal line intersects the curve at point P. From point P, move upward until you reach the x axis. You should get to 7 on the x axis. Therefore, the solution to [tex]g(x) = -8[/tex] is [tex]x = 7[/tex]. In other words, [tex]g(7) = -8[/tex]. This ultimately means [tex]g^{-1}(-8) = 7[/tex]

Refer to the diagram below.

Ver imagen jimthompson5910